Biological complexes bases upon bacterium Pseudomonas fluorenscens and matters of stimulating nature, and their impact on plant growth and development - M. Solomiichuk (Карантин і захист рослин)
Goal. The analysis of biocomplex combinations with stimulating nature preparations and different derivative ammonium salts of dihidropirimidine and their efficience study.